2022
DOI: 10.14814/phy2.15409
|View full text |Cite
|
Sign up to set email alerts
|

Platelet polyphosphate and energy metabolism in professional male athletes (soccer players): A cross‐sectional pilot study

Abstract: Human platelet polyphosphate (polyP) is a multifunctional molecule; however, its functions are not yet fully understood. A recent study demonstrated that similar to skeletal muscle, polyP is involved in energy metabolism in platelets, which suggests that well-trained athletes may exhibit elevated platelet polyP levels for energy storage. To test this hypothesis, we quantified platelet polyP along with NADH, a component involved in ATP production in non-trained and well-trained male Japanese participants of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 35 publications
1
19
2
Order By: Relevance
“…Reciprocal conversion between ATP and polyP is thought to occur depending on the metabolic activity. This possibility was observed in a previous study of professional athletes [ 10 ]. We also found that such reciprocal conversion rarely occurs in the platelets of non-athletes at rest.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Reciprocal conversion between ATP and polyP is thought to occur depending on the metabolic activity. This possibility was observed in a previous study of professional athletes [ 10 ]. We also found that such reciprocal conversion rarely occurs in the platelets of non-athletes at rest.…”
Section: Discussionsupporting
confidence: 56%
“…Platelet polyP cellular metabolism, subcellular localization, and individual variability have all been poorly investigated because of the lack of clarity and controversy around the analytical methodologies. In a recent study [ 10 ] using modified DAPI-based methods, we suggested that energy metabolism, that is, the reciprocal conversion between ATP and polyP, could vary between professional athletes and non-athletes. We studied the impact of metabolic inhibitors and energy supplements on polyP levels to further explore the mechanism underlying this difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we believe that several other factors modulate the therapeutic potential of PRP through potentiation and suppression and are present in individual PRP preparations [30]. The candidate factor that we have recently paid attention to is polyphosphate (polyP) [31][32][33][34][35][36][37]. PolyP is an ancient, but still mysterious, biopolymer that is produced in the mitochondria in the extension of the ATP production line [33,34,38] and stored in the dense granules of platelets.…”
Section: Introductionmentioning
confidence: 99%
“…The candidate factor that we have recently paid attention to is polyphosphate (polyP) [31][32][33][34][35][36][37]. PolyP is an ancient, but still mysterious, biopolymer that is produced in the mitochondria in the extension of the ATP production line [33,34,38] and stored in the dense granules of platelets. Upon platelet activation, polyP is released alongside growth factors, and this impacts the immunological functions of platelets in addition to hemostatic function [32].…”
Section: Introductionmentioning
confidence: 99%